2013
DOI: 10.1038/nsmb.2667
|View full text |Cite
|
Sign up to set email alerts
|

Cycles in spatial and temporal chromosomal organization driven by the circadian clock

Abstract: Dynamic transitions in the epigenome have been associated with regulated patterns of nuclear organization. The accumulating evidence that chromatin remodeling is implicated in circadian function prompted us to explore whether the clock may control nuclear architecture. We applied the 3C-derived 4C technology (Chromosome Conformation Capture on Chip) in mouse embryonic fibroblasts (MEFs) to demonstrate the presence of circadian long-range interactions, using the clock-controlled Dbp gene as bait. The circadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 76 publications
8
107
1
Order By: Relevance
“…A recent study implicated the circadian machinery in determining temporal and spatial cycles of chromosomal organization and is capable of affecting the physical organization of the nuclear landscape via involvement of E-box elements (59). The diurnal variation of hGH1 transcript levels raises the possibility that the hGH1 locus can transit between an active and inactive chromosomal conformation in a cyclic manner daily.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study implicated the circadian machinery in determining temporal and spatial cycles of chromosomal organization and is capable of affecting the physical organization of the nuclear landscape via involvement of E-box elements (59). The diurnal variation of hGH1 transcript levels raises the possibility that the hGH1 locus can transit between an active and inactive chromosomal conformation in a cyclic manner daily.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is relevant, because SIRT1 modulates circadian gene expression (6,9,19). Hence, intranuclear territories presenting different redox ratios could serve as a regulatory layer for circadian transcription through SIRT1 or restrict circadian transcription to subnuclear domains (41,55). An interesting case is the transcription factor CtBP that can sense free NADH, resulting in controlling its binding affinity to specific interacting proteins (40).…”
Section: Discussionmentioning
confidence: 99%
“…The first demonstration that circadian genes are organized in functional nuclear territories was obtained by chromosome conformation capture on chip (4C) technology (71). This comprehensive study was carried out in mouse embryonic fibroblasts (MEFs) and demonstrated cyclic chromosomal arrangements using the circadian gene Dbp as bait.…”
Section: Oscillations In 3d: Revealing the Circadian Interactomementioning
confidence: 99%
“…This comprehensive study was carried out in mouse embryonic fibroblasts (MEFs) and demonstrated cyclic chromosomal arrangements using the circadian gene Dbp as bait. This gene is located in a highly gene-dense genomic environment, and its interchromosomal contacts are largely stable during the circadian cycle (71). Remarkably, a number of specific, cyclic variations in Dbp genomic interactions occur, thereby defining a circadian interactome ( Fig.…”
Section: Oscillations In 3d: Revealing the Circadian Interactomementioning
confidence: 99%